2016
DOI: 10.1007/s10549-016-3828-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of trastuzumab emtansine (T-DM1) in patients with HER2-positive breast cancer with brain metastases

Abstract: Few data are currently available regarding the efficacy and safety of T-DM1 in breast cancer (BC) patients with unselected brain metastases (BM), since most clinical trials have excluded BM patients or have only included highly selected patients. HER2 + BC patients with BM treated with T-DM1 in 5 French centers were included in this retrospective study. Clinical management was performed according to the product guidelines. Efficacy was evaluated recording tumor response rates, progression-free (PFS) and overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(51 citation statements)
references
References 39 publications
2
48
0
1
Order By: Relevance
“…7 A recently published case series of 39 patients with brain metastases treated with T-DM1 reported a median time to brain progression of 8.6 months, with progression in the brain occurring as the first site of progression in 19 patients (48.7%), of whom only three had concurrent extra-cranial progression. 8 Similar to our study population, these patients had received a median of two prior lines of chemotherapy for advanced breast cancer, but in contrast, all patients had progressive brain disease when they commenced T-DM1. Despite this, their rate of brain progression on T-DM1 is similar to the rate (9/16, 56.3%) we report here in the 16 patients with known brain metastases, for whom the median brainspecific PFS was 9.9 months.…”
Section: Discussionmentioning
confidence: 84%
“…7 A recently published case series of 39 patients with brain metastases treated with T-DM1 reported a median time to brain progression of 8.6 months, with progression in the brain occurring as the first site of progression in 19 patients (48.7%), of whom only three had concurrent extra-cranial progression. 8 Similar to our study population, these patients had received a median of two prior lines of chemotherapy for advanced breast cancer, but in contrast, all patients had progressive brain disease when they commenced T-DM1. Despite this, their rate of brain progression on T-DM1 is similar to the rate (9/16, 56.3%) we report here in the 16 patients with known brain metastases, for whom the median brainspecific PFS was 9.9 months.…”
Section: Discussionmentioning
confidence: 84%
“…However, in our study, we found that only the patients with HR-/HER2+ have a relatively better prognosis in brain metastasis. In fact, studies have shown that targeted drug herceptin can prolong the survival in breast cancer patients with brain metastases [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Systemic therapies including trastuzumab emtansine (T-DM1) can be effective in treating patients with HER2 þ breast cancer with central nervous system (CNS) disease, with T-DM1 showing improved median survival without increased risk for CNS progression compared with capecitabine-lapatinib in the EMILIA trial (6,7). Jacot and colleagues have also shown T-DM1 to be safe and effective in patients with HER2 þ breast cancer with brain metastases (8).…”
Section: Introductionmentioning
confidence: 99%